PENERAPAN MODEL PEMBELAJARAN TGT UNTUK MENINGKATKAN HASIL BELAJAR, PARTISIPASI, DAN SIKAP SISWA - Nyoman Sudimahayasa (Jurnal Pendidikan dan Pengajaran, 2015)
Abstract: The Implementation of TGT Learning Model to Improve Achievement, Participation, and Attitude of Tenth Grade Students. This research aimed at improving students achievement, participation, and attitude on a training course Technical Drawing Interpretation as the results of the implementation instructional type of Team Game Tournament.The researchwas a class-room action research conducted in two cycles with the subjects of Class X TSM 1 of students at SMKN 3 Singaraja in the academic year 2013/2014.The data sources were formative tests conducted at the end of every cycle, classroom observation, and questionnaire for the students. Data were ana-lyzed descriptively to know the improvement of students’ achievement in the training course, to ex-plain the active participation of students during the teaching and learning process, and also to explain the students’ attitude towards the implementation of TGT in the course. The findings of the research revealed that there was an improvement in students’ achievement, from the average score of 52.19 in the pre-cycle, 69.84 at the end of Cycle 1, and 76.41 in Cycle 2. The research also found that stu-dents became very actively participated in the class and also had very positive views towards the im-plementation of TGT in the classroom. Keywords: achievement, attitude, participation, Team Games Tournament (TGT) Abstrak: Penerapan Model Pembelajaran TGT untuk Meningkatkan Hasil Belajar, Partisipasi dan Sikap Siswa. Penelitian ini bertujuan untuk meningkatkan hasil belajar siswa pada mata diklat Menginterpretasikan Gambar Teknik dan sekaligus mengetahui keaktifan siswa sebagai akibat penerapan pembelajaran tipe Teams-Games Tournament (TGT) pada proses pembelajaran mata diklat tersebut. Penelitian ini adalah penelitian tindakan kelas yang dilakukan dalam 2 siklus dengan subyek penelitian adalah siswa kelas X TSM1 SMKN 3 Singaraja pada tahun ajaran 2013/2014. Sumber data diambil dari tes di akhir setiap siklus, observasi kelas dan angket pendapat siswa tentang implementasi TGT. Data dianalisis secara deskriptif untuk menjelaskan peningkatan hasil belajar serta keaktifan siswa dalam proses pembelajaran serta tanggapan siswa terhadap pembelajaran yang menerapkan tipe TGT. Hasil penelitian ini menunjukan adanya peningkatan hasil belajar siswa dari sebelum dan setelah menerapkan model pembelajaran TGT pada mata diklat Menginterpretasikan Gambar Teknik, dimana nilai rata-rata siswa yang sebelumnya 52,19 pada pra siklus meningkat menjadi 69,84 pada akhir Siklus 1 dan menjadi 76,41 pada akhir Siklus 2. Hasil penelitian juga menunjukan partisipasi aktif dan tanggapan positif siswa dalam implementasi TGT di kelas TSM1. Kata-kata kunci: hasil belajar, partisipasi, sikap, Team Games Tournament (TGT)